Stool frequency and form and gastrointestinal symptoms differ by day of the menstrual cycle in healthy adult women taking oral contraceptives: a prospective observational study - Taylor C. Judkins; Jennifer C. Dennis-Wall; Shireen Madani Sims; James Colee; Bobbi Langkamp-Henken (BMC, 2020)
Abstract Background Little is known about how the menstrual cycle affects gastrointestinal function and self-reported stress in young, healthy women taking oral contraceptives (OC). This study prospectively characterized gastrointestinal function and symptoms on each day throughout the menstrual cycle. Methods Healthy women aged 18-35 years (n = 78) who took OC participated in the 5-week observational study. Stool frequency, self-reported stress, stool form measured by the Bristol Stool Form Scale (BSFS), and gastrointestinal symptoms measured by a modified version of the Gastrointestinal Symptom Rating Scale (GSRS) were assessed daily. GSRS scores were reported (1 = no discomfort at all, 7 = very severe discomfort) and were averaged for individual syndrome scores or summed for the total score. The validated, weekly version of the GSRS was completed at two time points to reflect menstruation and 1 week prior to menstruation (n = 72). Outcomes were analyzed in linear mixed models with the Dunnett's post hoc test against day 1 of menstrual bleeding or with nonparametric tests. Results Daily stress (P = 0.0018), BSFS score (P = 0.0493), stool frequency (P = 0.0241), abdominal pain (P < 0.0001), diarrhea (P = 0.0022), constipation (P = 0.0446), reflux (P = 0.0193), and indigestion (P < 0.0001) all varied significantly by the day of the menstrual cycle. Dunnett's post hoc tests showed that scores (mean ± SEM) on the first day of bleeding (day 1) for daily abdominal pain (2.6 ± 0.2), diarrhea (1.7 ± 0.1), and indigestion (2.1 ± 0.2) symptoms were higher than scores on all other days of the menstrual cycle (P < 0.05) with scores not on day 1 falling under 1.5, or between no discomfort at all and slight discomfort. Reflux, stool frequency, BSFS, self-reported stress, and constipation were higher on day 1 (P < 0.05) than on 12, 8, 6, 4, and 2 other days of the menstrual cycle, respectively. The median (IQR) GSRS score was higher during the week of menstruation than the week prior to menstruation for diarrhea [1.50 (1.00-2.33) vs 1.33 (1.00-2.00), P = 0.002] and abdominal pain [2.00 (1.33-2.67) vs 1.67 (1.33-2.33), P = 0.011] syndrome scores. Conclusion Bowel habits appear to vary across the menstrual cycle and suggest more gastrointestinal discomfort on day 1 of menstrual bleeding in healthy women taking OC. Future interventional studies could identify ways to improve gastrointestinal symptoms in healthy women during menstruation.